2014
DOI: 10.3354/sedao00006
|View full text |Cite
|
Sign up to set email alerts
|

Secondary sexual characters and spermatophores of Solenocera agassizii (Decapoda: Solenoceridae), including a comparison with other solenocerid shrimp

Abstract: Solenocera agassizii is commercially exploited along the Costa Rican Pacific coast and represents around 30% of the country's total shrimp catch. Despite its economic importance, information on its biology is scarce. Here we describe its secondary sexual characters and spermatophores. The open thelycum is located between Sternites XIII and XIV. A pair of parallel setose projections (Sternite XIV) is distally curved in larger females (< 30 mm carapace length); a disk-shaped projection (Sternite XIII) emerges fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Accordingly, the SMM obtained in the present study should coincide with the size at which the thelycum of S. agassizii is fully developed. This assumption is corroborated by the fact that SMM obtained in the present study coincides with the minimum size at which spermatophores were found attached to the thelycum (from 28.5 mm CL) (Villalobos-Rojas & Wehrtmann, 2014).…”
Section: Discusionsupporting
confidence: 88%
See 1 more Smart Citation
“…Accordingly, the SMM obtained in the present study should coincide with the size at which the thelycum of S. agassizii is fully developed. This assumption is corroborated by the fact that SMM obtained in the present study coincides with the minimum size at which spermatophores were found attached to the thelycum (from 28.5 mm CL) (Villalobos-Rojas & Wehrtmann, 2014).…”
Section: Discusionsupporting
confidence: 88%
“…This species represented up to 30 % of the total shrimp landings of Costa Rica between 2001 and, with the highest yearly landings in 1986 (2.6 x 10 6 kg) (Wehrtmann & Nielsen-Muñoz, 2009) followed by a continued reduction since 2005 (0.57 x 10 6 kg) to roughly 0.0061 x 10 6 kg in 2014 (Instituto Costarricense de Pesca y Acuicultura [INCOP-ESCA]). Despite this alarming situation and the economic importance of this species, the knowledge about the biology of S. agassizii is rather limited (Villalobos-Rojas & Wehrtmann, 2011;Rodríguez et al, 2012;Villalobos-Rojas & Wehrtmann, 2014). Such a scenario hinders any effort to develop an appropriate management plan for the sustainable exploitation of this resource.…”
mentioning
confidence: 99%